Two new species of Abelocephala (Heteroptera: Reduviidae) from Taiwan - Forthman, Michael (Zootaxa, 2021)
The millipede assassin bug genus Abelocephala Maldonado, 1996 (Heteroptera: Reduviidae: Ectrichodiinae: Abelocephalini) is currently comprised of seven Oriental species. Two macropterous males, representing two new species, were recently collected from Taiwan in Malaise trap samples: A. baliensis sp. nov. and A. yilanensis sp. nov. Habitus and structural images are provided for each new species. A revised diagnosis of Abelocephala and an updated identification key to all species of the genus are given.